2006
DOI: 10.3748/wjg.v12.i37.5959
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis on human hepatocarcinoma cell lines by an alkyl resorcinol isolated fromLithraea molleoides

Abstract: INTRODUCTIONHepatocellular carcinoma is the 5 th most common cancer in the world and the 4 th most common cause of cancer-associated mortality [1] . Surgical resection and local treatment are frequently limited, as a result of metastasis, cirrhosis, and other pathological changes in the liver parenchyma. The development of chemotherapeutic or chemopreventive agents for hepatocellular carcinoma is important to reduce the mortality caused by this disease. Since cell homeostasis depends on the balance between pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Both of these two compounds are reported to be associated with antibacterial 19,20 and anticancer 21,22 properties. Resorcinol structure is present in large number of compounds of therapeutic value showing anticancer 23,24 and antifungal activity 25,26 . A novel series of quinols with heteroaromatic or (arylsulphonyl) indole substitution at 4 position has been reported to show in vitro antitumour activity 27 .…”
Section: Short Communicationmentioning
confidence: 99%
“…Both of these two compounds are reported to be associated with antibacterial 19,20 and anticancer 21,22 properties. Resorcinol structure is present in large number of compounds of therapeutic value showing anticancer 23,24 and antifungal activity 25,26 . A novel series of quinols with heteroaromatic or (arylsulphonyl) indole substitution at 4 position has been reported to show in vitro antitumour activity 27 .…”
Section: Short Communicationmentioning
confidence: 99%
“…To date, several compounds that show antimicrobial, antiparasitic, antitumoral and genotoxic activities have been identified among the alkylresorcinols (Picardo et al 1987;Lytollis et al 1995;Singh et al 1995;Kozubek et al 2001). In addition, their potential use in the therapy and/or prevention of specific classes of diseases has attracted particular attention (Itokawa et al 1989;Suresh & Ray 1990;Gasiorowsky et al 1996;Kozubek et al 2001;Filip et al 2002;Barbini et al 2006). Up to the present time, the cytotoxic activity of climacostol was assayed on a panel of protozoa, flatworms and crustacea, as well as on human cancer and non-cancer cell lines (Miyake et al 2003;Buonanno 2005;Buonanno et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant property of ARs as polyphenolic compounds originates from the ability of their hydroxyl groups to donate H to a free radical, or to donate one electron to an alkyl free radical, which breaks the chain reaction of lipid peroxidation. Thus, ARs may modulate cellular redox state and protect proteins, phospholipids, DNA, RNA, and carbohydrates against peroxidation [82,84,85,87].…”
Section: Biological Activity Of Alkylresorcinolsmentioning
confidence: 99%
“…Ten in vitro studies [58,84,[96][97][98][99][100][101][102][103] were identified and included in the analysis of natural and synthetic ARs for activities that inhibit growth of human cancer cells ( Table 2). The studies focused on isolation and identification of naturally occurring ARs and their synthesis.…”
Section: Cytotoxic Activities Of Alkylresorcinolsmentioning
confidence: 99%
See 1 more Smart Citation